Bismuth tungstate-based heterojunction photocatalyst, preparation method thereof and application of bismuth tungstate-based heterojunction photocatalyst in organic wastewater treatment
The existing tungstate is solved by introducing copper ytterbium bimetal doped carbon dots and carbon dot modified cobalt disulfide into the bismuth tungstate catalyst to form a bismuth tungstate heterojunction photocatalyst and depositing silver on its surface. The problem of low efficiency of bismuth catalysts has achieved efficient organic pollutant degradation capabilities.
Patent Information
- Application Number
- CN202411422412.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing bismuth tungstate-based catalysts are inefficient in degrading complex organic pollutants, mainly due to their shorter light-generating electron-hole limitations on lifetime and visible light response areas.
Cobalt disulfide and bismuth tungstate complex modified by copper ytterbium bimetal doped carbon dots and carbon dots are prepared by ultrasonic dispersion and hot water reaction, and silver is deposited on its surface to form CuYb-CDs@CoS2@Zr-Bi2WO6-Ag catalyst enhances its catalytic activity and light absorption capacity.
It significantly improves the activity of the catalyst, can produce reactive oxygen species efficiently under visible light, and further improves the oxygen production efficiency under ultrasound, significantly improving the degradation ability of organic dye pollutants.
Smart Images

Figure CN119259082A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of bismuth-based heterojunction materials and water treatment, and in particular to a bismuth tungstate-based heterojunction photocatalyst, a preparation method thereof and application in organic wastewater treatment. Background Art
[0002] With the rapid development of the economy and society and the rapid advancement of industrialization and urbanization, the sewage discharged by urban residents in their daily lives and the wastewater generated by industrial enterprises contain a large amount of organic pollutants. Such organic pollutants can easily flow into urban rivers through surface water, causing serious pollution of the water environment, thus having an adverse impact on the sustainable green development of the city.
[0003] As a kind of advanced oxidation technology, semiconductor photocatalytic oxidation technology has been applied in pollutant degradation in recent years due to its mild reaction conditions, strong oxidation ability, environmental protection and economy. Among many visible light responsive metal oxide semiconductors, bismuth tungstate-based catalysts have become a research hotspot in the photocatalytic removal of organic pollutants in wastewater due to their suitable band gap width and special layered structure. However, due to the limitation of its short photogenerated electron-hole pair lifetime and visible light response region, its efficiency in degrading complex organic pollutants is affected (Hou Zongliang, Zhao Pingge, Xiao Zhengyang, et al. Preparation of bismuth tungstate-based photocatalysts and research progress in their degradation of organic pollutants in water [J]. Applied Chemical Industry, 2023, 52(10):2915-2919.).
[0004] Therefore, it is now necessary to improve the conventional bismuth tungstate-based catalyst materials to enhance their activity in catalyzing the degradation of organic matter in water. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a bismuth tungstate-based heterojunction photocatalyst, a preparation method thereof and an application thereof in organic wastewater treatment in view of the deficiencies in the above-mentioned prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: to provide a method for preparing a bismuth tungstate-based heterojunction photocatalyst, comprising the following steps: 1) Preparation of copper-ytterbium bimetallic doped carbon dots; 2) Preparation of carbon dot-modified cobalt disulfide: 2-1) adding the copper-yttrium bimetallic doped carbon dots prepared in step 1) into deionized water and performing ultrasonic dispersion to obtain a carbon dot dispersion; 2-2) Take CoCl 2 6H 2 O、Na 2 S 2 O 3 6H 2O was added into deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed. The obtained mixture was transferred into a polytetrafluoroethylene-lined reactor and reacted under heating. After the reaction, centrifugation was performed, and the solid product was washed and vacuum dried to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 ; 3) Preparation of carbon dot-modified cobalt disulfide-doped bismuth tungstate complex: Bismuth salt, zirconium oxychloride and carbon dot-modified cobalt disulfide were added to deionized water and ultrasonically dispersed; Na 2 WO 4 ·2H 2 O and sodium dodecyl sulfate, ultrasonically dispersed, the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor, heated and reacted, centrifuged after the reaction, and the solid product was washed and vacuum dried to obtain a carbon dot-modified cobalt disulfide bismuth tungstate complex, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 ; 4) In CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 Silver is deposited on the surface to obtain a bismuth tungstate-based heterojunction photocatalyst.
[0007] Preferably, step 1) is specifically: 1-1) adding glucose, L-cysteine and tetraphenylporphyrin to an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, stirring to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O、Yb(NO 3 ) 3 ·5H 2 O, benzoic acid were added into deionized water and stirred to obtain mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the mixture is reacted under heating. After the reaction is completed, the mixture is cooled to room temperature and filtered. The filtrate is dialyzed in deionized water using a dialysis bag, and the dialyzate in the dialysis bag is freeze-dried to obtain copper-ytterbium bimetallic doped carbon dots, which are denoted as CuYb-CDs.
[0008] Preferably, step 1) is specifically: 1-1) Add 360-1440 mg of glucose, 60-242 mg of L-cysteine, and 230-900 mg of tetraphenylporphyrin to 75-300 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at a temperature of 60-70° C., and stir for 2-10 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 181-726mg, Yb(NO 3 ) 3 ·5H 2 O 112-450 mg and benzoic acid 244-976 mg are added to 75-300 mL of deionized water at a temperature of 60-70°C, and stirred for 5-30 minutes to obtain a mixture 2; 1-3) Add mixture 1 to mixture 2 under stirring, and ultrasonically disperse for 30-90 minutes to obtain a carbon dot precursor solution; then add the carbon dot precursor solution into a polytetrafluoroethylene-lined reactor, react at 170-220° C. for 4-16 hours, cool to room temperature after the reaction, filter with a 0.22 μm filter membrane, and dialyze the filtrate in deionized water for 12-48 hours using a dialysis bag with a molecular weight cutoff of 1000-1500 Da. The dialyzate in the dialysis bag is freeze-dried to obtain copper-ytterbium bimetallic doped carbon dots.
[0009] Preferably, step 1) is specifically: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 363mg, Yb(NO 3 ) 3 ·5H 2 O 225 mg and benzoic acid 488 mg were added into 150 mL of deionized water at 70 °C and stirred for 10 min to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da, and the water is changed every 8 hours. The dialysate in the dialysis bag is freeze-dried to obtain copper-ytterbium bimetallic doped carbon dots.
[0010] Preferably, step 2) is specifically: 2-1) taking 0.3-1 g of the copper-yttrium bimetallic doped carbon dots prepared in step 1) and adding them into 50-200 mL of deionized water, and ultrasonically dispersing them for 15-60 min to obtain a carbon dot dispersion; 2-2) Take 1.5-6mmol of CoCl 2 6H 2 O, 1.5-6mmol Na 2 S 2 O 3 6H 2 O was added into 15-60 mL of deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed at 50-75 ° C for 10-40 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor, and reacted at 140-180 ° C for 5-20 h. After cooling to room temperature, centrifugal separation was performed, and the solid product was washed with deionized water and ethanol in turn, and vacuum dried at 40-70 ° C for 3-12 h to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 .
[0011] Preferably, step 3) is specifically: Take 485-1500 mg of Bi(NO 3 ) 3 ·5H 2 O, 64-250 mg ZrOCl 2 8H 2 O and 40-160 mg of carbon dot-modified cobalt disulfide were added to 100-500 mL of deionized water and ultrasonically dispersed for 15-60 min; 150-600 mg of Na 2 WO 4 ·2H 2 O and 17-70 mg of sodium dodecyl sulfate, ultrasonically disperse for 15-60 min, transfer the resulting mixture to a polytetrafluoroethylene-lined reactor, react at 170-190 ° C for 12-48 h, cool to room temperature after the reaction, centrifuge, wash the solid product with deionized water, and vacuum dry at 80-100 ° C for 8-24 h to obtain a bismuth tungstate complex doped with carbon dots modified with cobalt disulfide.
[0012] Preferably, step 4) is specifically: 4-1) Take CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex was added into deionized water and ultrasonically dispersed to obtain a mixture A; 4-2) Take AgNO 3Add deionized water, add aqueous ammonia dropwise while stirring, and stop adding dropwise when a precipitate appears in the solution and just disappears, to obtain a mixture B; 4-3) Add glucose to deionized water and stir to obtain mixture C; 4-4) Add mixture B dropwise to mixture A under light-shielding conditions, keep stirring, then add mixture C, stir and react, centrifuge and filter after the reaction, wash the solid product with deionized water, and vacuum dry to obtain the final product: bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag.
[0013] Preferably, step 4) is specifically: 4-1) Take 313-1252 mg CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex is added into 100-400 mL of deionized water and ultrasonically dispersed for 30-120 min to obtain a mixture A; 4-2) Take 7-34 mg of AgNO 3 Add 25-100 mL of deionized water, and dropwise add 0.02-0.1 mol / L of aqueous ammonia under stirring, and stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B; 4-3) Add 5-20 mg of glucose into 15-60 mL of deionized water and stir for 2-10 min to obtain a mixture C; 4-4) Add mixture B dropwise into mixture A under stirring under light-shielding conditions, keep stirring, then add mixture C, and react at 20-40°C with stirring for 12-48 hours. After the reaction is completed, centrifuge and filter the solid product with deionized water, and vacuum dry at 55-80°C for 3-12 hours to obtain a bismuth tungstate-based heterojunction photocatalyst.
[0014] The present invention also provides a bismuth tungstate-based heterojunction photocatalyst, which is prepared by the method as described above.
[0015] The present invention also provides an application of the bismuth tungstate-based heterojunction photocatalyst as described above in organic wastewater treatment, and the application method is: adding the bismuth tungstate-based heterojunction photocatalyst to the organic wastewater treatment, and treating the wastewater under visible light irradiation and simultaneous application of ultrasound.
[0016] The beneficial effects of the present invention are: The present invention provides a catalyst based on a multi-modified bismuth tungstate-based heterojunction, which can significantly improve its catalytic activity through a composite multi-effect modification treatment, and enable the catalyst to not only generate active oxygen under visible light, but also have the ability to efficiently generate active oxygen under ultrasonic excitation, which can greatly improve the ability of the catalyst to degrade organic dye pollutants in wastewater.
[0017] In the present invention, the surface of copper-ytterbium bimetallic doped carbon dots CuYb-CDs has abundant carboxyl, amino and hydroxyl functional groups, which can efficiently generate reactive oxygen species ROS (such as hydroxyl radicals •OH), singlet oxygen 1 O2), ROS has the ability to decompose organic matter, thus making the carbon dots active in degrading organic dyes in wastewater; in addition, the carbon dots have inherited the sonosensitive properties of tetraphenylporphyrin, which enables them to be excited to produce reactive oxygen under ultrasound, and the acoustic-optical dual response characteristics can improve their reactive oxygen production efficiency; thirdly, the doping of Cu and Yb can increase the electron cloud density, reduce the recombination rate of photogenerated electrons and holes, and improve the efficiency of carbon dots in producing reactive oxygen. The doping of Yb can form heterojunctions, reduce the band gap, enhance light absorption, and accelerate the separation and transfer of photogenerated electrons and holes, thereby improving the catalytic activity of carbon dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the infrared spectrum of the copper-ytterbium bimetallic doped carbon dots CuYb-CDs synthesized in Example 1; Figure 2 It is the test result of singlet oxygen production ability; Figure 3 The rhodamine B degradation performance test results of the bismuth tungstate-based heterojunction photocatalysts prepared in Examples 1-4 and Comparative Examples 1-4; Figure 4 The degradation rate of Rhodamine B after 60 minutes of treatment with the bismuth tungstate-based heterojunction photocatalyst prepared in Examples 1-4 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0020] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0021] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0022] A first aspect of the present invention provides a bismuth tungstate-based heterojunction photocatalyst and a preparation method thereof, the method comprising the following steps: 1) Preparation of Cu-Yb bimetallic doped carbon dots: 1-1) Add 360-1440 mg of glucose, 60-242 mg of L-cysteine, and 230-900 mg of tetraphenylporphyrin to 75-300 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at a temperature of 60-70° C., and stir for 2-10 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 181-726mg, Yb(NO 3 ) 3 ·5H 2 O 112-450 mg and benzoic acid 244-976 mg are added to 75-300 mL of deionized water at a temperature of 60-70°C, and stirred for 5-30 minutes to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 30-90 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 170-220° C. for 4-16 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered through a 0.22 μm filter membrane, and the filtrate is dialyzed in deionized water for 12-48 hours using a dialysis bag with a molecular weight cutoff of 1000-1500 Da. The dialyzate in the dialysis bag is freeze-dried to obtain copper ytterbium bimetallic doped carbon dots, which are recorded as CuYb-CDs.
[0023] 2) Preparation of carbon dot-modified cobalt disulfide: 2-1) taking 0.3-1 g of the copper-yttrium bimetallic doped carbon dots prepared in step 1) and adding them into 50-200 mL of deionized water, and ultrasonically dispersing them for 15-60 min to obtain a carbon dot dispersion; 2-2) Take 1.5-6mmol of CoCl 2 6H 2 O, 1.5-6mmol Na 2 S 2 O 3 6H 2O was added into 15-60 mL of deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed at 50-75 ° C for 10-40 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor, and reacted at 140-180 ° C for 5-20 h. After cooling to room temperature, centrifugal separation was performed, and the solid product was washed with deionized water and ethanol in turn, and vacuum dried at 40-70 ° C for 3-12 h to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 .
[0024] 3) Preparation of carbon dot-modified cobalt disulfide-doped bismuth tungstate complex: Take 485-1500 mg of Bi(NO 3 ) 3 ·5H 2 O, 64-250 mg ZrOCl 2 8H 2 O and 40-160 mg of carbon dot-modified cobalt disulfide were added to 100-500 mL of deionized water and ultrasonically dispersed for 15-60 min; 150-600 mg of Na 2 WO 4 ·2H 2 O and 17-70 mg of sodium dodecyl sulfate were ultrasonically dispersed for 15-60 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 170-190 ° C for 12-48 h. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 80-100 ° C for 8-24 h to obtain a carbon dot-modified cobalt disulfide bismuth tungstate complex, which was recorded as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 .
[0025] 4) Surface deposition of silver: 4-1) Take 313-1252 mg CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex is added into 100-400 mL of deionized water and ultrasonically dispersed for 30-120 min to obtain a mixture A; 4-2) Take 7-34 mg of AgNO 3 Add 25-100 mL of deionized water, and dropwise add 0.02-0.1 mol / L of aqueous ammonia under stirring, and stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B; 4-3) Add 5-20 mg of glucose into 15-60 mL of deionized water and stir for 2-10 min to obtain a mixture C; 4-4) Add mixture B dropwise to mixture A under light-shielding conditions, keep stirring, then add mixture C, stir and react at 20-40°C for 12-48h, centrifuge and filter after the reaction, wash the solid product with deionized water, and vacuum dry at 55-80°C for 3-12h to obtain a bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag.
[0026] The second aspect of the present invention provides the application of the above-mentioned bismuth tungstate-based heterojunction photocatalyst in the treatment of organic wastewater, and the application method is: adding the bismuth tungstate-based heterojunction photocatalyst to the organic wastewater treatment, and treating the wastewater under visible light irradiation and simultaneous application of ultrasound.
[0027] In a preferred embodiment, the concentration of bismuth tungstate-based heterojunction photocatalyst added to wastewater is 0.1-10 g / L, the ultrasonic power applied is 100-800 W, and the ultrasonic frequency is 20-120 kHz. The specific process conditions are conventionally selected according to the type and concentration of pollutants in the wastewater and the treatment requirements.
[0028] 1) Preparation of copper-ytterbium bimetallic doped carbon dots; 2) Preparation of carbon dots modified cobalt disulfide: CuYb-CDs@CoS 2 ; 3) Preparation of Bismuth Tungstate Composite Doped with Carbon Dots Modified Cobalt Disulfide: CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 ; 4) In CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 Silver is deposited on the surface to obtain a bismuth tungstate-based heterojunction photocatalyst.
[0029] The present invention provides a catalyst based on a multi-modified bismuth tungstate-based heterojunction, which can significantly improve its catalytic activity through a composite multi-effect modification treatment, and enable the catalyst to not only generate active oxygen under visible light, but also have the ability to efficiently generate active oxygen under ultrasonic excitation, which can greatly improve the ability of the catalyst to degrade organic dye pollutants in wastewater.
[0030] The main preparation process of the present invention is as follows: (1) First, glucose, L-cysteine, tetraphenylporphyrin and benzoic acid were used as the main raw material components, Cu 2+ , Yb 3+As the doping component, a copper-ytterbium bimetallic doped carbon dots CuYb-CDs were prepared by hydrothermal method; (2) Then, the in-situ modified copper-ytterbium bimetallic carbon dots (CuYb-CDs@CoS) were prepared by hydrothermal reaction. 2 In this reaction, CuYb-CDs and CoCl 2 6H 2 After mixing with O, the carboxyl and hydroxyl functional groups on the surface of carbon dots can coordinate with Co2+ and electrostatic adsorption to connect Co2+ to CuYb-CDs, and then the hydrothermal reaction can realize the bonding between CuYb-CDs and CoS 2 Strong grafting; (3) Then, metal zirconium and CuYb-CDs@CoS were prepared by a hot water reaction. 2 Co-doped bismuth tungstate-based heterojunction to obtain CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 Composite, during this reaction, CuYb-CDs@CoS 2 With Bi(NO 3 ) 3 ·5H 2 O、ZrOCl 2 8H 2 After mixing with CuYb-CDs@CoS, the coordination and electrostatic adsorption of Bi3+, Zr4+ and CuYb-CDs@CoS can be achieved through the carboxyl and hydroxyl functional groups on the surface of the carbon dots and the Bi3+ ions. 2 Connection, followed by hydrothermal reaction to achieve CuYb-CDs@CoS 2 With Zr-Bi 2 WO 6 Strong grafting; (4) Finally, silver ammonia solution was used as the silver source to realize the silver element in CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The surface deposition load gives the final product: CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag, namely bismuth tungstate-based heterojunction photocatalyst.
[0031] The main mechanism of action of each component doped in the bismuth tungstate-based heterojunction photocatalyst is as follows: 1. The surface of CuYb-CDs is rich in carboxyl, amino and hydroxyl functional groups, which can efficiently generate reactive oxygen species (ROS) (such as hydroxyl radicals •OH) and singlet oxygen under the action of visible light.1 O2), ROS has the ability to decompose organic matter, which makes the carbon dots active in degrading organic dyes in wastewater; in addition, the carbon dots have inherited the sonosensitive properties of tetraphenylporphyrin, so that they can be excited to produce reactive oxygen under ultrasound, and the acoustic-optical dual response characteristics can improve their reactive oxygen production efficiency; thirdly, the doping of Cu and Yb can increase the electron cloud density, reduce the recombination rate of photogenerated electrons and holes, and improve the efficiency of carbon dots in producing reactive oxygen. Yb doping can form heterojunctions, narrow the band gap, enhance light absorption ability, and accelerate the separation and transfer of photogenerated electrons and holes (Cheng Yan. Preparation of rare earth doped bismuth oxyfluoride-based heterojunction materials and research on their photocatalytic properties [D]. Liaoning University, 2022.), thereby improving the catalytic activity of carbon dots.
[0032] 2. Carbon dots and CoS 2 Graft, CoS 2 It can effectively inhibit the combination of photogenerated electrons and holes, further enhancing the catalytic activity of carbon dots; at the same time, after being doped into the bismuth tungstate-based heterojunction photocatalyst system, CoS 2 Load to Bi 2 WO 6 The heterojunction is constructed on the CoS 2 Can reduce Bi 2 WO 6 The band gap energy of Bi can be increased, the effective spacing of electron-hole pairs can be increased, and the transport of charge carriers can be promoted (Ma Xin, Qian Xiang, Fan Xiaoqiang, et al. Preparation of supported CoS2 / Bi2WO6 and study of its photocatalytic performance [J]. Chemical Reaction Engineering and Technology, 2020. DOI: 10.11730 / j.issn.1001-7631.2020.04.0297.10.), which can also enhance the photocatalytic performance of Bi 2 WO 6 In addition, uYb-CDs@CoS 2 With Zr-Bi 2 WO 6 The grafting can also increase the specific surface area of the material and the number of active sites, and also make the carbon dots and CoS 2 It can achieve better dispersion in the catalyst system, which is beneficial to improving the efficiency of catalytic degradation of organic matter.
[0033] 3.Bi 2 WO 6 Zirconium doping with Zr can narrow the band gap of bismuth tungstate, thereby enhancing its absorption of visible light. It also helps to improve the separation efficiency of photogenerated carriers and reduce the recombination of electrons and holes, thereby increasing the rate and efficiency of photocatalytic reactions.
[0034] 4. In CuYb-CDs@CoS2 @Zr-Bi 2 WO 6 The silver element loaded on the surface has a plasma resonance effect, and the plasma resonance peak of the silver element is in the visible light region, thus enhancing the absorption capacity of visible light (Yin Lu. Research on the preparation, modification and photocatalytic performance of bismuth tungstate [D]. Hebei Normal University [2024-10-10]. DOI: CNKI: CDMD: 2.1017.147103.), which is very important for CuYb-CDs@CoS 2 and Zr-Bi 2 WO 6 The improvement of photocatalytic activity is very beneficial.
[0035] Therefore, in the bismuth tungstate-based heterojunction photocatalyst structure system of the present invention, CuYb-CDs, CoS 2 、Zr-Bi 2 WO 6 The components directly cooperate with each other to achieve a synergistic enhancement effect on the performance of the catalyst in degrading organic matter.
[0036] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0037] Example 1 A bismuth tungstate-based heterojunction photocatalyst, the preparation method of which comprises the following steps: 1) Preparation of Cu-Yb bimetallic doped carbon dots: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 363mg, Yb(NO 3 ) 3 ·5H 2 O 225 mg and benzoic acid 488 mg were added into 150 mL of deionized water at 70 °C and stirred for 10 min to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da. The dialysate in the dialysis bag is freeze-dried to obtain copper ytterbium bimetallic doped carbon dots, which are recorded as CuYb-CDs.
[0038] 2) Preparation of carbon dot-modified cobalt disulfide: 2-1) 0.6 g of the copper-yttrium bimetallic carbon dots prepared in step 1) was added into 100 mL of deionized water and ultrasonically dispersed for 30 min to obtain a carbon dot dispersion; 2-2) Take 3 mmol of CoCl 2 6H 2 O, 3mmol of Na 2 S 2 O 3 6H 2 O was added into 30 mL of deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed at 70 °C for 20 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 160 °C for 10 h. After cooling to room temperature, it was centrifuged and the solid product was washed with deionized water and ethanol in turn, and vacuum dried at 50 °C for 6 h to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 .
[0039] 3) Preparation of carbon dot-modified cobalt disulfide-doped bismuth tungstate complex: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O, 128 mg ZrOCl 2 8H 2 O and 80 mg of carbon dot-modified cobalt disulfide were added to 200 mL of deionized water and ultrasonically dispersed for 30 min. 300 mg of Na 2 WO 4 ·2H 2 O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 175 ° C for 24 h. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90 ° C for 12 h to obtain a carbon dot-modified cobalt disulfide bismuth tungstate complex, which was recorded as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 .
[0040] 4) Surface deposition of silver: 4-1) Take 626 mg CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex was added into 150 mL of deionized water and ultrasonically dispersed for 60 min to obtain mixture A; 4-2) Take 17 mg of AgNO 3 Add 50 mL of deionized water, and dropwise add 0.05 mol / L of aqueous ammonia under stirring. Stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B. 4-3) Add 10 mg of glucose into 30 mL of deionized water and stir for 5 min to obtain mixture C; 4-4) Mixture B was added dropwise to mixture A under light-shielding conditions, and the mixture was stirred. Mixture C was then added and stirred at 40°C for 24 hours. After the reaction, the solid product was centrifuged and filtered. The solid product was washed with deionized water and dried under vacuum at 75°C for 6 hours to obtain the final product: bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag.
[0041] Example 2 A bismuth tungstate-based heterojunction photocatalyst, the preparation method of which comprises the following steps: 1) Preparation of Cu-Yb bimetallic doped carbon dots: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 363mg, Yb(NO 3 ) 3 ·5H 2 O 225 mg and benzoic acid 488 mg were added into 150 mL of deionized water at 70 °C and stirred for 10 min to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da. The dialysate in the dialysis bag is freeze-dried to obtain copper ytterbium bimetallic doped carbon dots, which are recorded as CuYb-CDs.
[0042] 2) Preparation of carbon dot-modified cobalt disulfide: 2-1) 0.6 g of the copper-yttrium bimetallic doped carbon dots prepared in step 1) was added into 100 mL of deionized water and ultrasonically dispersed for 30 min to obtain a carbon dot dispersion; 2-2) Take 3 mmol of CoCl 2 6H 2 O, 3mmol of Na 2 S 2 O 3 6H 2 O was added into 30 mL of deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed at 70 °C for 20 min. The obtained mixture was transferred into a polytetrafluoroethylene-lined reactor, and reacted at 170 °C for 8 h. After cooling to room temperature, it was centrifuged and the solid product was washed with deionized water and ethanol in turn, and vacuum dried at 50 °C for 6 h to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 .
[0043] 3) Preparation of carbon dot-modified cobalt disulfide-doped bismuth tungstate complex: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O, 128 mg ZrOCl 2 8H 2 O and 80 mg of carbon dot-modified cobalt disulfide were added to 200 mL of deionized water and ultrasonically dispersed for 30 min. 300 mg of Na 2 WO 4 ·2H 2 O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 165 ° C for 24 h. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90 ° C for 12 h to obtain a carbon dot-modified cobalt disulfide bismuth tungstate complex, which was recorded as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 .
[0044] 4) Surface deposition of silver: 4-1) Take 626 mg CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex was added into 150 mL of deionized water and ultrasonically dispersed for 60 min to obtain mixture A; 4-2) Take 15 mg of AgNO 3 Add 50 mL of deionized water, and dropwise add 0.05 mol / L of aqueous ammonia under stirring. Stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B. 4-3) Add 10 mg of glucose into 30 mL of deionized water and stir for 5 min to obtain mixture C; 4-4) Mixture B was added dropwise to mixture A under light-shielding conditions, and the mixture was stirred. Mixture C was then added and stirred at 35°C for 24 hours. After the reaction, the solid product was centrifuged and filtered. The solid product was washed with deionized water and dried under vacuum at 75°C for 6 hours to obtain the final product: bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag.
[0045] Example 3 A bismuth tungstate-based heterojunction photocatalyst, the preparation method of which comprises the following steps: 1) Preparation of Cu-Yb bimetallic doped carbon dots: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 363mg, Yb(NO 3 ) 3 ·5H 2 O 225 mg and benzoic acid 488 mg were added into 150 mL of deionized water at 70 °C and stirred for 10 min to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da. The dialysate in the dialysis bag is freeze-dried to obtain copper ytterbium bimetallic doped carbon dots, which are recorded as CuYb-CDs.
[0046] 2) Preparation of carbon dot-modified cobalt disulfide: 2-1) 0.6 g of the copper-yttrium bimetallic doped carbon dots prepared in step 1) was added into 100 mL of deionized water and ultrasonically dispersed for 30 min to obtain a carbon dot dispersion; 2-2) Take 3 mmol of CoCl 2 6H 2 O, 3mmol of Na 2 S 2 O 3 6H 2 O was added into 30 mL of deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed at 70 °C for 20 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor, and reacted at 155 °C for 12 h. After cooling to room temperature, it was centrifuged and the solid product was washed with deionized water and ethanol in turn, and vacuum dried at 50 °C for 6 h to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 .
[0047] 3) Preparation of carbon dot-modified cobalt disulfide-doped bismuth tungstate complex: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O, 110 mg ZrOCl 2 8H 2 O and 78 mg of carbon dot-modified cobalt disulfide were added to 200 mL of deionized water and ultrasonically dispersed for 30 min. 300 mg of Na 2 WO 4 ·2H 2 O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 175 ° C for 24 h. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90 ° C for 12 h to obtain a carbon dot-modified cobalt disulfide bismuth tungstate complex, which was recorded as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 .
[0048] 4) Surface deposition of silver: 4-1) Take 626 mg CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex was added into 150 mL of deionized water and ultrasonically dispersed for 60 min to obtain mixture A; 4-2) Take 20 mg of AgNO 3 Add 50 mL of deionized water, and dropwise add 0.05 mol / L of aqueous ammonia under stirring. Stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B. 4-3) Add 10 mg of glucose into 30 mL of deionized water and stir for 5 min to obtain mixture C; 4-4) Mixture B was added dropwise to mixture A under light-shielding conditions, and the mixture was stirred. Mixture C was then added and stirred at 40°C for 24 hours. After the reaction, the solid product was centrifuged and filtered. The solid product was washed with deionized water and dried under vacuum at 75°C for 6 hours to obtain the final product: bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag.
[0049] Example 4 A bismuth tungstate-based heterojunction photocatalyst, the preparation method of which comprises the following steps: 1) Preparation of Cu-Yb bimetallic doped carbon dots: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 363mg, Yb(NO 3 ) 3 ·5H 2 O 225 mg and benzoic acid 488 mg were added into 150 mL of deionized water at 70 °C and stirred for 10 min to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da. The dialysate in the dialysis bag is freeze-dried to obtain copper ytterbium bimetallic doped carbon dots, which are recorded as CuYb-CDs.
[0050] 2) Preparation of carbon dot-modified cobalt disulfide: 2-1) 0.5 g of the copper-yttrium bimetallic carbon dots prepared in step 1) was added into 100 mL of deionized water and ultrasonically dispersed for 30 min to obtain a carbon dot dispersion; 2-2) Take 3 mmol of CoCl 2 6H 2 O, 3mmol of Na 2 S 2 O 3 6H 2 O was added into 30 mL of deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed at 70 °C for 20 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 160 °C for 10 h. After cooling to room temperature, it was centrifuged and the solid product was washed with deionized water and ethanol in turn, and vacuum dried at 50 °C for 6 h to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS 2 .
[0051] 3) Preparation of carbon dot-modified cobalt disulfide-doped bismuth tungstate complex: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O, 135 mg ZrOCl 2 8H 2 O and 70 mg of carbon dot-modified cobalt disulfide were added to 200 mL of deionized water and ultrasonically dispersed for 30 min. 300 mg of Na 2 WO 4 ·2H 2 O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 175 ° C for 24 h. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90 ° C for 12 h to obtain a carbon dot-modified cobalt disulfide bismuth tungstate complex, which was recorded as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 .
[0052] 4) Surface deposition of silver: 4-1) Take 626 mg CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 The complex was added into 150 mL of deionized water and ultrasonically dispersed for 60 min to obtain mixture A; 4-2) Take 15 mg of AgNO 3 Add 50 mL of deionized water, and dropwise add 0.05 mol / L of aqueous ammonia under stirring. Stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B. 4-3) Add 10 mg of glucose into 30 mL of deionized water and stir for 5 min to obtain mixture C; 4-4) Mixture B was added dropwise to mixture A under light-shielding conditions, and the mixture was stirred. Mixture C was then added and stirred at 40°C for 24 hours. After the reaction, the solid product was centrifuged and filtered. The solid product was washed with deionized water and dried under vacuum at 75°C for 6 hours to obtain the final product: bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS 2 @Zr-Bi 2 WO 6 -Ag.
[0053] Comparative Example 1 A bismuth tungstate-based heterojunction photocatalyst, the preparation method of which comprises the following steps: 1) Preparation of zirconium-doped bismuth tungstate composite: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O, 128 mg ZrOCl 2 8H 2 O was added to 200 mL of deionized water and ultrasonically dispersed for 30 min; 300 mg of Na 2 WO 4 ·2H 2 O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 175 ° C for 24 h. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90 ° C for 12 h to obtain a zirconium-doped bismuth tungstate composite, which was recorded as Zr-Bi 2 WO 6 .
[0054] 2) Surface deposition of silver: 2-1) 626 mg of zirconium-doped bismuth tungstate complex was added into 150 mL of deionized water and ultrasonically dispersed for 60 min to obtain a mixture A; 2-2) Take 17 mg of AgNO 3 Add 50 mL of deionized water, and dropwise add 0.05 mol / L of aqueous ammonia under stirring. Stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B. 2-3) Add 10 mg of glucose into 30 mL of deionized water and stir for 5 min to obtain mixture C; 2-4) Add mixture B dropwise into mixture A under stirring under light-shielding conditions, keep stirring, then add mixture C, and react at 40°C with stirring for 24 hours. After the reaction is completed, centrifuge and filter, wash the solid product with deionized water, and vacuum dry at 75°C for 6 hours to obtain the final product: bismuth tungstate-based heterojunction photocatalyst.
[0055] Comparative Example 2 A bismuth tungstate-based heterojunction photocatalyst, the preparation method of which comprises the following steps: 1) Preparation of cobalt disulfide: 1-1) Take 3 mmol of CoCl 2 6H 2 O, 3mmol of Na 2 S 2 O 3 6H 2 O was added into 30 mL of deionized water and ultrasonically dispersed at 70 °C for 20 min. The obtained mixture was transferred into a polytetrafluoroethylene-lined reactor and reacted at 160 °C for 10 h. After cooling to room temperature, it was centrifuged and the solid product was washed with deionized water and ethanol in turn and dried in vacuo at 50 °C for 6 h to obtain cobalt disulfide.
[0056] 2) Preparation of bismuth tungstate composite doped with cobalt disulfide: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O, 128 mg ZrOCl 2 8H 2 O and 80 mg of cobalt disulfide were added to 200 mL of deionized water and ultrasonically dispersed for 30 min; 300 mg of Na 2 WO 4 ·2H 2O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 minutes, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 175°C for 24 hours. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90°C for 12 hours to obtain a bismuth tungstate complex doped with cobalt disulfide.
[0057] 3) Surface deposition of silver: 3-1) 626 mg of bismuth tungstate complex doped with cobalt disulfide was added into 150 mL of deionized water and ultrasonically dispersed for 60 min to obtain mixture A; 3-2) Take 17 mg of AgNO 3 Add 50 mL of deionized water, and dropwise add 0.05 mol / L of aqueous ammonia under stirring. Stop dropping when a precipitate appears in the solution and just disappears, to obtain a mixture B. 3-3) Add 10 mg of glucose into 30 mL of deionized water and stir for 5 min to obtain mixture C; 3-4) Add mixture B dropwise into mixture A under stirring under light-shielding conditions, keep stirring, then add mixture C, and react at 40°C with stirring for 24 hours. After the reaction is completed, centrifuge and filter, wash the solid product with deionized water, and vacuum dry at 75°C for 6 hours to obtain the final product: bismuth tungstate-based heterojunction photocatalyst.
[0058] Comparative Example 3 This example is basically the same as Example 1, except that: In this example, copper-doped carbon dots are used to replace the copper-ytterbium bimetallic-doped carbon dots in Example 1. The preparation method of the copper-doped carbon dots is as follows: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Cu(NO 3 ) 2 ·3H 2 O 363 mg and benzoic acid 488 mg were added into 150 mL of deionized water at 70 °C and stirred for 10 min to obtain mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da. The dialysate in the dialysis bag is freeze-dried to obtain copper-doped carbon dots, which are recorded as Cu-CDs.
[0059] Comparative Example 4 This example is basically the same as Example 1, except that: In this example, step 3) is as follows: Take 970 mg of Bi(NO 3 ) 3 ·5H 2 O and 80 mg of carbon dot-modified cobalt disulfide were added to 200 mL of deionized water and ultrasonically dispersed for 30 min. 300 mg of Na 2 WO 4 ·2H 2 O and 35 mg of sodium dodecyl sulfate were ultrasonically dispersed for 30 minutes, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 175°C for 24 hours. After the reaction, it was cooled to room temperature and centrifuged. The solid product was washed with deionized water and vacuum dried at 90°C for 12 hours to obtain a bismuth tungstate complex doped with carbon dots and modified with cobalt disulfide.
[0060] Then, silver is deposited on the carbon dot-modified cobalt disulfide bismuth tungstate complex prepared above by the method of step 4) in Example 1 to obtain a bismuth tungstate-based heterojunction photocatalyst.
[0061] 1. Performance Characterization 1. Reference Figure 1 , is the infrared spectrum of the CuYb-CDs synthesized in Example 1. It can be seen that the surface of the carbon dots contains abundant amino, carboxyl, hydroxyl and other functional groups, among which 748 cm -1 The peak at comes from the absorption peak of =CH on the pyrrole ring.
[0062] 2. Singlet oxygen production capacity detection The carbon dots synthesized in Example 1 and Comparative Example 3 were used to prepare carbon dot solutions with a concentration of 0.1 mg / mL, and then a singlet oxygen green fluorescent probe (SOSG, product number: KM0040, Beijing Biolab Technology Co., Ltd.) was used to detect the singlet oxygen content in the carbon dot solution at different times under the following test conditions.
[0063] (1) Only visible light illumination (power 500 W, λ>400 nm) was used to test the singlet oxygen content generated by the carbon dots synthesized in Example 1 at different times, which was recorded as CuYb-CDs-1#(HV).
[0064] (2) Visible light illumination (power 500 W, λ>400 nm) and ultrasound (ultrasonic power 450 W, ultrasonic frequency 100 kHz) were applied simultaneously to test the singlet oxygen content generated by the carbon dots synthesized in Example 1 and Comparative Example 3 at different times. Example 1 was recorded as CuYb-CDs-1#(HV+US), and Comparative Example 3 was recorded as CuCDs-3#(HV+US) in turn. Test results such as Figure 2 As shown, it can be seen that for the copper-ytterbium bimetallic doped carbon dots CuYb-CDs prepared in Example 1, applying ultrasound can produce more singlet oxygen than not applying ultrasound, which verifies the acousto-optic dual response characteristics of the carbon dots. The results of CuCDs-3# (HV+US) show that the doping of Yb in the carbon dots is beneficial to improving the singlet oxygen yield of the carbon dots.
[0065] 2. Degradation performance test The bismuth tungstate-based heterojunction photocatalysts prepared in Examples 1-4 and Comparative Examples 1-4 were respectively subjected to degradation tests of organic wastewater according to the following method.
[0066] A 40 mg / L Rhodamine B solution (volume 100 mL) was used as the target degradation product to simulate organic wastewater. A doped modified bismuth ferrite-based heterojunction was added to the solution at an addition amount of 1 g / L. After stirring for 10 minutes under light-proof conditions, the solution was transferred to a xenon lamp and irradiated with visible light (power 500 W, λ>400 nm). Ultrasonic action was applied during the process, with an ultrasonic power of 450 W and an ultrasonic frequency of 100 kHz. Samples were taken every 5 minutes, and the absorbance of the solution was tested with a UV-visible spectrophotometer (554 nm) to obtain the concentration of Rhodamine B, and the degradation rate of Rhodamine B was calculated as follows: ; In addition, a control example was set up. The control example used the bismuth tungstate-based heterojunction photocatalyst prepared in Example 1. No ultrasonic action was applied during the test, and the rest was the same as above.
[0067] Test results such as Figure 1 (Example 2-4 is not shown in the figure), the degradation rate results after 60 minutes of treatment are shown in the following Table 1: Table 1 According to the test results, the bismuth tungstate-based heterojunction photocatalysts prepared in Examples 1-3 can efficiently decompose rhodamine B under the combined action of visible light and ultrasound; when the ultrasound is removed, the decomposition efficiency decreases significantly (control example), which verifies the acoustic-optical dual-response catalytic activity of the bismuth tungstate-based heterojunction photocatalyst. The reason for the significant decrease in the degradation rate in Comparative Example 1 is that the catalyst system does not contain cobalt disulfide CuYb-CDs@CoS modified with carbon dots. 2The decrease in degradation rate in Comparative Example 2 is attributed to the undoped CuYb-CDs. The results of Comparative Example 3 show that Yb doped in the carbon dots has a promoting effect on improving the catalytic activity of the carbon dots. The results of Comparative Example 4 show that Bi 2 WO 6 Doping Zr in the catalyst can improve its ability to catalyze the degradation of organic matter.
[0068] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a bismuth tungstate-based heterojunction photocatalyst, characterized in that: The following steps are involved: 1) Preparation of copper-ytterbium bimetallic doped carbon dots; 2) Preparation of carbon dot modified cobalt disulfide: 2-1) adding the copper-yttrium bimetallic doped carbon dots prepared in step 1) into deionized water and performing ultrasonic dispersion to obtain a carbon dot dispersion; 2-2) CoCl2·6H2O and Na2S2O3·6H2O were added into deionized water, and the obtained mixture was added into the carbon dot dispersion under stirring, and ultrasonic dispersion was performed. The obtained mixture was transferred into a polytetrafluoroethylene-lined reactor, and reacted under heating. After the reaction, centrifugation was performed, and the solid product was washed and vacuum dried to obtain carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS2; 3) Preparation of bismuth tungstate complex doped with carbon dots modified cobalt disulfide: Bismuth salt, zirconium oxychloride and carbon dot-modified cobalt disulfide were added to deionized water and ultrasonically dispersed; Na2WO4·2H2O and sodium dodecyl sulfate were added to the obtained mixture and ultrasonically dispersed; the obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted under heating. After the reaction was completed, the mixture was centrifuged and separated. The solid product was washed and vacuum dried to obtain a bismuth tungstate composite doped with carbon dot-modified cobalt disulfide, which was recorded as CuYb-CDs@CoS2@Zr-Bi2WO6; 4) Silver was deposited on the surface of CuYb-CDs@CoS2@Zr-Bi2WO6 to obtain a bismuth tungstate-based heterojunction photocatalyst.
2. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 1, characterized in that: Step 1) is as follows: 1-1) adding glucose, L-cysteine and tetraphenylporphyrin to an ethanol aqueous solution consisting of deionized water and ethanol in a volume ratio of 1:1, stirring to obtain a mixture 1; 1-2) Add Cu(NO3)2·3H2O, Yb(NO3)3·5H2O and benzoic acid into deionized water and stir to obtain mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the mixture is reacted under heating. After the reaction is completed, the mixture is cooled to room temperature and filtered. The filtrate is dialyzed in deionized water using a dialysis bag, and the dialyzate in the dialysis bag is freeze-dried to obtain copper-ytterbium bimetallic doped carbon dots, which are denoted as CuYb-CDs.
3. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 2, characterized in that: Step 1) is as follows: 1-1) Add 360-1440 mg of glucose, 60-242 mg of L-cysteine, and 230-900 mg of tetraphenylporphyrin to 75-300 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at a temperature of 60-70° C., and stir for 2-10 minutes to obtain a mixture 1; 1-2) Add 181-726 mg of Cu(NO3)2·3H2O, 112-450 mg of Yb(NO3)3·5H2O, and 244-976 mg of benzoic acid into 75-300 mL of deionized water at 60-70°C, and stir for 5-30 minutes to obtain a mixture 2; 1-3) Add mixture 1 to mixture 2 under stirring, and ultrasonically disperse for 30-90 minutes to obtain a carbon dot precursor solution; then add the carbon dot precursor solution into a polytetrafluoroethylene-lined reactor, react at 170-220° C. for 4-16 hours, cool to room temperature after the reaction, filter with a 0.22 μm filter membrane, and dialyze the filtrate in deionized water for 12-48 hours using a dialysis bag with a molecular weight cutoff of 1000-1500 Da. The dialyzate in the dialysis bag is freeze-dried to obtain copper-ytterbium bimetallic doped carbon dots.
4. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 3, characterized in that: Step 1) is as follows: 1-1) Add 720 mg of glucose, 121 mg of L-cysteine, and 461 mg of tetraphenylporphyrin to 150 mL of an ethanol aqueous solution composed of deionized water and ethanol in a volume ratio of 1:1 at 70°C, and stir for 5 minutes to obtain a mixture 1; 1-2) Add 363 mg of Cu(NO3)2·3H2O, 225 mg of Yb(NO3)3·5H2O, and 488 mg of benzoic acid into 150 mL of deionized water at 70°C, and stir for 10 min to obtain a mixture 2; 1-3) Mixture 1 is added to mixture 2 under stirring, and ultrasonic dispersion is performed for 45 minutes to obtain a carbon dot precursor solution; then the carbon dot precursor solution is added to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 200°C for 8 hours. After the reaction is completed, it is cooled to room temperature and filtered through a 0.22 μm filter membrane. The filtrate is dialyzed in deionized water for 24 hours using a dialysis bag with a molecular weight cutoff of 1200 Da, and the water is changed every 8 hours. The dialysate in the dialysis bag is freeze-dried to obtain copper-ytterbium bimetallic doped carbon dots.
5. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 1, characterized in that: Step 2) is as follows: 2-1) taking 0.3-1 g of the copper-yttrium bimetallic doped carbon dots prepared in step 1) and adding them into 50-200 mL of deionized water, and ultrasonically dispersing them for 15-60 min to obtain a carbon dot dispersion; 2-2) Take 1.5-6mmol CoCl2·6H2O and 1.5-6mmol Na2S2O3·6H2O and add them to 15-60mL deionized water. The resulting mixture is added to the carbon dot dispersion under stirring, and ultrasonically dispersed at 50-75°C for 10-40min. The resulting mixture is transferred to a polytetrafluoroethylene-lined reactor, reacted at 140-180°C for 5-20h, cooled to room temperature and centrifuged, and the solid product is washed with deionized water and ethanol in turn, and vacuum dried at 40-70°C for 3-12h to obtain carbon dot-modified cobalt disulfide, which is recorded as CuYb-CDs@CoS2.
6. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 1, characterized in that: Step 3) is as follows: Take 485-1500 mg of Bi(NO3)3·5H2O, 64-250 mg of ZrOCl2·8H2O and 40-160 mg of carbon dot-modified cobalt disulfide, add them to 100-500 mL of deionized water, and ultrasonically disperse them for 15-60 min; add 150-600 mg of Na2WO4·2H2O and 17-70 mg of sodium dodecyl sulfate to the obtained mixture, and ultrasonically disperse them for 15-60 min. The obtained mixture is transferred to a polytetrafluoroethylene-lined reactor, and reacted at 170-190°C for 12-48 hours. After the reaction is completed, it is cooled to room temperature and centrifuged. The solid product is washed with deionized water and vacuum dried at 80-100°C for 8-24 hours to obtain a bismuth tungstate complex doped with carbon dot-modified cobalt disulfide.
7. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 1, characterized in that: Step 4) is as follows: 4-1) Add the CuYb-CDs@CoS2@Zr-Bi2WO6 composite into deionized water and disperse it by ultrasonic to obtain a mixture A; 4-2) Add AgNO3 to deionized water, add aqueous ammonia dropwise while stirring, and stop adding dropwise when a precipitate appears in the solution and just disappears, to obtain a mixture B; 4-3) Add glucose to deionized water and stir to obtain mixture C; 4-4) Add mixture B dropwise into mixture A under stirring under light-shielding conditions, keep stirring, then add mixture C and react by stirring. After the reaction is completed, centrifuge and filter the solid product. Wash the solid product with deionized water and vacuum dry to obtain the final product: bismuth tungstate-based heterojunction photocatalyst, denoted as CuYb-CDs@CoS2@Zr-Bi2WO6-Ag.
8. The method for preparing the bismuth tungstate-based heterojunction photocatalyst according to claim 7, characterized in that: Step 4) is as follows: 4-1) 313-1252 mg of CuYb-CDs@CoS2@Zr-Bi2WO6 composite was added to 100-400 mL of deionized water and ultrasonically dispersed for 30-120 min to obtain a mixture A; 4-2) Take 7-34 mg of AgNO3 and add it to 25-100 mL of deionized water. Add 0.02-0.1 mol / L of aqueous ammonia dropwise while stirring. Stop adding dropwise when a precipitate appears in the solution and disappears, to obtain a mixture B. 4-3) Add 5-20 mg of glucose into 15-60 mL of deionized water and stir for 2-10 min to obtain a mixture C; 4-4) Add mixture B dropwise into mixture A under stirring under light-shielding conditions, keep stirring, then add mixture C, and react at 20-40°C with stirring for 12-48 hours. After the reaction is completed, centrifuge and filter the solid product with deionized water, and vacuum dry at 55-80°C for 3-12 hours to obtain a bismuth tungstate-based heterojunction photocatalyst.
9. A bismuth tungstate-based heterojunction photocatalyst, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. An application of the bismuth tungstate-based heterojunction photocatalyst as claimed in claim 9 in the treatment of organic wastewater, the application method being: adding the bismuth tungstate-based heterojunction photocatalyst to the treatment of organic wastewater, and treating the wastewater under visible light irradiation and simultaneous application of ultrasound.
Citation Information
Patent Citations
Single-layer bismuth tungstate nano-sheet composite photocatalyst modified by carbon quantum dots, preparation method of photocatalyst and application
CN106902810A
Bismuth tungstate composite photocatalyst modified by nitrogen-doped carbon quantum dot and preparation method and application thereof
CN107224990A
Preparation method and application of copper-doped CQD (carbon quantum dot) / bismuth tungstate composite photocatalyst
CN108786787A
Preparation method and application of multielement Cu<2>O@CQDs / Bi<2>WO<6> composite photocatalyst
CN108940300A
Carbon quantum dot / bismuth tungstate heterojunction and preparation method and application thereof
CN116688974A